Psychological Education Health Assessment Problems Based on Improved Constructive Neural Network - Li, Yang; Li, Jia ze; Fan, Qi; Li, Xin; Wang, Zhihong (Frontiers in Psychology, 2022)
In order to better assess the mental health status, combining online text data and considering the problems of lexicon sparsity and small lexicon size in feature statistics of word frequency of traditional LIWC dictionary, and combining the advantages of CNN convolutional neural network in contextual semantic extraction, a CNN-based mental health assessment method is proposed and evaluated with the measurement indicators in CLPsych2017. The results showed that the results obtained from the mental health assessment by CNN were superior in all indicators, thus indicating the feasibility of CNN in mental health assessment.